Finite element modeling of textiles in Abaqus CAE - Ciesielska-Wrobel, Izabela (Boca Raton : CRC Press LLC, 2019)
The aim of the book is to provide engineers with a practical guide to Finite Element Modelling (FEM) in Abaqus CAE software. The guide is in the form of step-by-step procedures concerning yarns, woven fabric and knitted fabrics modelling, as well as their contact with skin so that the simulation of haptic perception between textiles and skin can be
4.2.3 The Load Plate4.2.4 Changing the Model and Using Different Visualizations; References; 5. Geometry of a Knit Structure; 5.1 Knit Structure; 5.2 Guide for Sketching a Simplified Loop; 5.3 Guide for Sketching a Profiled Loop; Index
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE -- Mechanics -- General; TECHNOLOGY -- Electricity; TECHNOLOGY -- Engineering -- Industrial; Abaqus (Electronic resource); Textile fabrics -- Mathematical models; Finite element method